Performance gap of two users in downlink full-duplex cooperative NOMA - Tu-Trinh Nguyen; Dinh-Thuan Do (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
A full-duplex non-orthogonal multiple access (FD-NOMA) systems are expected to play a significant role in fifth generation (5G) networks, addressing spectrum efficiency and massive connections. In this regard, the feasibility of FD communications to improve spectrum utilization is main consideration in term of outage performance. Specifically, we derive exact formulas of outage probability for FD-NOMA, over Nakagami-m fading channels. Extensive analysis revealed that higher quality of channel leads to better performance. We verify expressions throughout Monte-Carlo simulations.